Bortezomib induces thrombocytopenia by the inhibition of proplatelet formation of megakaryocytes. (16th May 2014) - Murai, Kazunori; Kowata, Shugo; Shimoyama, Tadashi; Yashima‐Abo, Akiko; Fujishima, Yukiteru; Ito, Shigeki; Ishida, Yoji
Abstract Bortezomib is a potent proteasome inhibitor that has been extensively used to treat multiple myeloma. One of the most common grade 3 adverse events is cyclic thrombocytopenia. In this study, we studied the mechanism by which bortezomib induces thrombocytopenia in a mouse model. After the intravenous administration of bortezomib (2.5 mg/kg) via tail vein, platelet counts significantly decreased on days 2–4 and recovered to the normal range on day 6. Bortezomib (2.5 mg/kg) injected into mice in vivo did not affect colony‐forming unit‐megakaryocytes (CFU‐Mk) or megakaryocytes in the bone marrow. However, proplatelet formation (PPF) significantly decreased on days 2 and 4, after bortezomib administration to mice. Meanwhile, CFU‐Mk formation and the ploidy distribution of cultured megakaryocytes in vitro were not affected by bortezomib used at concentrations of ≤1 ng/mL. The PPF of megakaryocytes in vitro significantly decreased with 0.1, 1, 10, and 100 ng/mL bortezomib. Considering the bortezomib concentration in clinical studies, these data strongly suggest that decreased PPF activity induces thrombocytopenia. To elucidate the mechanism behind decreased PPF, Western blot was performed. Activated Rho expression increased after the incubation of murine platelets with bortezomib. Decreased PPF activity was eliminated by the addition of Y27632, a Rho kinase inhibitor, in vitro. Given that the Rho/Rho kinase pathway is a negative regulator of PPF, bortezomib increases activated Rho, inducing decreased PPF, which results in decreased platelet count.